2022
DOI: 10.24996/ijs.2022.63.10.3
|View full text |Cite
|
Sign up to set email alerts
|

Electropolymerization of [N-(1, 3-thiazo-2-yl)] maleamic acid and their Nanocomposite with Graphene Oxide as Protective Coating against Corrosion and Antibacterial Action

Abstract: Poly [N-(1, 3-thiazo-2yl)]maleamic acid synthesized from corresponding monomer N-(1, 3-thiazo-2yl)maleamic acid (NTM) by using the process of electrochemical polymerization in aqueous solution at room temperature. The structure of the polymeric layer generated on the surface of (Low Carbon Steel (L.C.S)) (working electrode) was investigated by Fourier Transmission Infrared [FT-IR] and a scanning electron microscope [SEM]. The anticorrosion ability of a polymeric layer on low carbon steel (L.C.S) was investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…The following Eq. 2 is used to determine the protection efficacy 14,15 %Pe =[(Icor. The cathodic and anodic Tafel plots in a solution of 3.5% NaCl were used to calculate the corrosion potential (Ecor) and corrosion current density (Icor) of the SS316L that had not been coated with PE before to and after.…”
Section: Resultsmentioning
confidence: 99%
“…The following Eq. 2 is used to determine the protection efficacy 14,15 %Pe =[(Icor. The cathodic and anodic Tafel plots in a solution of 3.5% NaCl were used to calculate the corrosion potential (Ecor) and corrosion current density (Icor) of the SS316L that had not been coated with PE before to and after.…”
Section: Resultsmentioning
confidence: 99%
“…The corrosion current density (i corr ) and corrosion potential (E corr ) were achieved at the intersection of the anodic and cathodic currentpotential curves. The electrochemical characteristics for the LCS disc in 3.5% NaCl solution with and without PACC and PACC-metal oxides nanocomposite are shown in Table 3 by Tafel plots (i corr , E corr , C.R, PL,  a , and  c ) [35]. Equation ( 2) was used to calculate the protection efficiency, PE% (included in Table 3), using the i corr values [36]:…”
Section: Corrosion Testsmentioning
confidence: 99%
“…It has been demonstrated that using nano particles in polymer coatings can improve not only the barrier effects but also the electrochemical anticorrosion and other performance characteristics such as adhesions, thermal stabilities, mechanical strengths, magnetonstatic shielding, and hydrophobic properties 12,13 . Many different kinds of oxides nano particles, such as TiO2, ZnO, Al2O3, CeO2, SiO2 and Nano clays, were applied to polymer coating and shown superior protective properties than standard polymer coating [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%